2017
DOI: 10.1111/jen.12397
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, insecticidal and biochemical effects of Melaleuca alternifolia essential oil on the Helicoverpa armigera

Abstract: Pesticide resistance has developed as a result of long-term and extensive use of chemical pesticides. Essential oils from aromatic plants may provide a new and safe alternative to conventional insecticides. In this study, the insecticidal activities of the essential oil of Melaleuca alternifolia and their chemical constituents against Helicoverpa armigera Hubner were investigated, and the underlying mechanisms were studied. The essential oil showed distinct antifeedant (AFC 50 = 8.93 mg/ml) and good contact (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 46 publications
3
63
0
1
Order By: Relevance
“…Glucose, total protein and total lipid contents on the beetle extracts were determined by the O -toluidine method described by Hafiz et al [ 78 ]. Aspartate aminotransferase (AST), and alanine aminotransferase (ALT) protein activities were determined as previously described [ 79 ].…”
Section: Methodsmentioning
confidence: 99%
“…Glucose, total protein and total lipid contents on the beetle extracts were determined by the O -toluidine method described by Hafiz et al [ 78 ]. Aspartate aminotransferase (AST), and alanine aminotransferase (ALT) protein activities were determined as previously described [ 79 ].…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the prevention and control of H. armigera is largely dependent on chemical pesticides [ 4 ]. However, total reliance on the application of synthetic insecticides to control H. armigera has not achieved the desired success, and has resulted in the emergence of pesticide resistance, environmental contamination, toxicity to non-target organisms, disruption of ecological balance, and health hazards [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The insecticidal properties of essential oils are primarily attributed to the blend of various major and minor phytochemicals. Content assessment analysis for ten major components in the M. alternifolia were predetermined by GC/MS and reported in our previous study [ 35 ], which indicated that the major constituents terpinen-4-ol (40.09%), γ-terpinene (21.85%), α-terpinene (11.34%), α-terpineol (6.91%), α-pinene (5.86%), terpinolene (3.24%), 1,8-cineole (1.83%) limonene (1.20%), p-cymene (1.36%), and sabinene (0.20%) were within the range specified according to Inter-national Organization for Standardization standard 4730.…”
Section: Methodsmentioning
confidence: 99%